ANALISIS STRUKTUR DAN KOMPOSISI VEGETASI PADA HUTAN KELOLA MASYARAKATAN (HKM) HARAPAN JAYA BATU AMPAR, NAGARI PANTI, KECAMATAN PANTI, KABUPATEN PASAMAN TIMUR, SUMATRA BARAT - Tiara Dwi Ananda; Irma Leilani Eka Putri; Reki Kardiman; Filza Yulina Ade; Azwir Anhar; Ryan Thanoesya; Bayu Riangga Hanafi (Universitas Cokroaminoto Palopo, 2026)
Vegetation structure refers to the stratification of plant growth stages within an ecosystem, which are generally classified into seedling, sapling, pole, and tree levels. Analysis of plant composition aims to identify plant species present in a forest area. This study aimed to determine the vegetation structure and plant composition in the Community Forest Management (HKM) area of Harapan Jaya Batu Ampar, Nagari Panti, Panti District, East Pasaman Regency, West Sumatra. The research employed a nested quadrat method with plots placed randomly, consisting of 10 plots adjusted to the field conditions at the study site. The results showed that the 2 × 2 m and 5 × 5 m plots were dominated by the family Rubiaceae, with Coffea robusta as the most abundant species. The 10 × 10 m plots were dominated by the family Lauraceae, with Litsea sp. as the dominant species. Meanwhile, the 20 × 20 m plots were dominated by the family Fagaceae, with Lithocarpus elegans recorded as the main species. These findings provide preliminary data for understanding the vegetation structure in the Community Forest Management (HKM) area of Harapan Jaya Batu Ampar, Nagari Panti, Panti District, East Pasaman Regency, West Sumatra